'You're only there on the phone'? A qualitative exploration of community, affect and agential capacity in HIV self‐testing using a smartphone app. Issue 3 (26th February 2021) - Janssen, Ricky; Engel, Nora; Pant Pai, Nitika; Esmail, Aliasgar; Dheda, Keertan; Thomas, Réjean; Krumeich, Anja
Abstract: Mobile health (mHealth) technologies for HIV care are developed to provide diagnostic support, health education, risk assessment and self‐monitoring. They aim to either improve or replace part of the therapeutic relationship. Part of the therapeutic relationship is affective, with the emergence of feelings and emotion, yet little research on mHealth for HIV care focuses on affect and HIV testing practices. Furthermore, most of the literature exploring affect and care relations with the introduction of mHealth is limited to the European and Australian context. This article explores affective dimensions of HIV self‐testing using a smartphone app strategy in Cape Town, South Africa and Montréal, Canada. This study is based on observation notes, 41 interviews and 1 focus group discussion with study participants and trained HIV healthcare providers from two quantitative studies evaluating the app‐based self‐test strategy. Our paper reveals how fear, apathy, judgement, frustration and comfort arise in testing encounters using the app and in previous testing experiences, as well as how this relates to care providers and test materials. Attending to affective aspects of this app‐based self‐testing practice makes visible certain affordances and limitations of the app within the therapeutic encounter and illustrates how mHealth can contribute to HIV care.